Evaluating Corrective Action Effectiveness Against Incident Recurrence in Mining Operations: A Hierarchy of Controls Approach (2023–2025) - Zinedina Salsabila Mustain; Doni Hikmat Ramdhan (Al-Hijrah Indonesia, 2026)
Incident recurrence indicates that organizational learning has not fully succeeded in breaking the chain of failure. This study aims to analyze the relationship between the quality of corrective actions, as measured by the Hierarchy of Controls, and incident recurrence, while accounting for incident characteristics as control variables, at PT XYZ (mining contractor) during 2023–2025. This quantitative study with a retrospective correlational design analyzed 124 incident investigation reports. Critical factors are classified using two schemes presented side by side, namely the company's internal taxonomy and the Human Factors Analysis and Classification System (HFACS). Analyses were conducted at univariate, bivariate (Fisher's Exact Test and Pearson Chi-Square), and multivariate (multiple logistic regression) levels. The reliability of corrective action scoring was validated through inter-rater agreement (weighted Kappa = 0.722; substantial). Results show a high recurrence rate under both schemes (65.3% under HFACS; 72.6% under the internal scheme). Critical Factor was the most dominant predictor (OR = 7.02; p < 0.001), followed by Incident Classification (OR = 8.91; p = 0.003), while Corrective Action Quality was not significant (p = 0.556), consistently across both schemes. Applying the HFACS taxonomy refined the dominant Human Error category (80.6%) into Violation (38.7%) and Error (41.1%), revealing a diversity of failure types useful for improving investigation. The study concludes that the effectiveness of recurrence prevention is determined more by the accuracy of root-cause diagnosis during investigation than by the technical level of corrective actions alone.